2020
DOI: 10.7717/peerj.8583
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of machine learning algorithms for predicting acute kidney injury after liver cancer resection

Abstract: Objective Machine learning methods may have better or comparable predictive ability than traditional analysis. We explore machine learning methods to predict the likelihood of acute kidney injury after liver cancer resection. Methods This is a secondary analysis cohort study. We reviewed data from patients who had undergone resection of primary hepatocellular carcinoma between January 2008 and October 2015. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…In the field of healthcare, accurate prognosis is essential for efficient management of patients while prioritizing care to the more needy. In order to aid in prognosis, several prediction models have been developed using various methods and tools including machine learning (Chen & Asch, 2017;Qu et al, 2019;Lei et al, 2020). Machine learning is a field of artificial intelligence where computers simulate the processes of human intelligence and can synthesize complex information from huge data sources in a short period of time (Benke & Benke, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the field of healthcare, accurate prognosis is essential for efficient management of patients while prioritizing care to the more needy. In order to aid in prognosis, several prediction models have been developed using various methods and tools including machine learning (Chen & Asch, 2017;Qu et al, 2019;Lei et al, 2020). Machine learning is a field of artificial intelligence where computers simulate the processes of human intelligence and can synthesize complex information from huge data sources in a short period of time (Benke & Benke, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As artificial intelligence develops at an extraordinarily pace, countless applications have been created in the past decade (28)(29)(30). Recently, AI has been increasingly adopted to diagnose and predict some diseases, while the medical image analysis community has paid particular attention to the success of machine learning in computer vision (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with conventional analysis methods, recent studies have suggested that some machine learning algorithms may reach greater accuracy than the conventional logistic regression models [75,102,103]. Studies have shown that machine learning can predict AKI after general surgery, liver transplant, cardiac surgery, hepatectomy, severe burns, sepsis, and percutaneous coronary intervention [75,[104][105][106][107][108][109][110]. Utilizing data from more than 700,000 subjects from multi-centers and stratified by an interval window of 6 hours, a recurrent neural network-based risk prediction model for AKI (AUC of 0.92] was verified [111].…”
Section: Predicting Csa-aki By Machine Learningmentioning
confidence: 99%